Application of Capnography Waveform Analyses for Evaluation of Recovery Process in a Patient with Heart Failure: A Case Report - Koyama, Takashi; Kobayashi, Masanori; Ichikawa, Tomohide; Wakabayashi, Yasushi; Abe, Hidetoshi (Archives of Clinical and Medical Case Reports, 2020)
Resting end-tidal CO2 levels obtained from capnography are associated with the severity of heart failure (HF). It has not been fully investigated whether other respiratory parameters acquired from detailed capnography waveform analyses could evaluate the recovery process in HF patients. In this case, the analysis of nasal capnography waveforms (diurnal five minutes recording) was performed to monitor and analyze end-tidal CO2 (ETCO2) values, inspiratory/expiratory ratio and respiratory intervals. We observed that these three parameters increased concurrently with decreasing plasma BNP levels during the recovery stage of HF. The kurtosis of frequency distributions of capnography waveforms became larger as HF improved. Proper utilization of these analyses could evaluate HF severity during the recovery process in patients with HF.